Australia's dangerous creatures : for dummies - Lofts, Graeme; Gill, Peg. (Milton, Qld. : Wiley Publishing Australia, 2008)
"Guide to Australian creatures that are deadly or may be dangerous."--Provided by publisher.
Includes index.
"Find out more about these fascinating animals and how to avoid a nasty encounter"--Cover.
Keywords: Dangerous animals -- Australia; Poisonous animals -- Australia